2014
DOI: 10.7448/ias.17.3.19149
|View full text |Cite
|
Sign up to set email alerts
|

Comparing patterns of sexual risk among adolescent and young women in a mixed‐method study in Tanzania: implications for adolescent participation in HIV prevention trials

Abstract: IntroductionDespite the disproportionate impact of HIV on women, and adolescents in particular, those below age 18 years are underrepresented in HIV prevention trials due to ethical, safety and logistical concerns. This study examined and compared the sexual risk contexts of adolescent women aged 15–17 to young adult women aged 18–21 to determine whether adolescents exhibited similar risk profiles and the implications for their inclusion in future trials.MethodsWe conducted a two-phase, mixed-method study to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 17 publications
0
7
1
Order By: Relevance
“…The same issues hinder parents’ and healthcare providers’ acceptance of adolescent girls’ sexuality and need for information and HIV protection. Moreover, developmentally adolescents may have difficulties accurately assessing their risk [ 77 ], planning ahead or controlling impulses. Results from FACTS 001 and VOICE showed that young women had more challenges with adherence than older women, especially when they did not have a single/primary partner and when they lived with their parents [ 78 ].…”
Section: Resultsmentioning
confidence: 99%
“…The same issues hinder parents’ and healthcare providers’ acceptance of adolescent girls’ sexuality and need for information and HIV protection. Moreover, developmentally adolescents may have difficulties accurately assessing their risk [ 77 ], planning ahead or controlling impulses. Results from FACTS 001 and VOICE showed that young women had more challenges with adherence than older women, especially when they did not have a single/primary partner and when they lived with their parents [ 78 ].…”
Section: Resultsmentioning
confidence: 99%
“…Young adults and women tend to have a high incidence of HIV, and play an important role in the ongoing transmission of HIV [26,27]. This strengthens the need for HIV vaccine trials and willingness to participate studies to target the largest number of women and young volunteers [28][29][30]. Our population consisted of young adults most-at-risk for HIV infection, of whom almost half were women, identified and recruited from the general community, in contrast to other HIV vaccine preparedness studies which specifically targeted populations that are vulnerable and socially stigmatized such as MSM and FSW [17,22,23,31].…”
Section: Plos Onementioning
confidence: 91%
“…Several papers in this supplement report on research targeting various groups of women for whom microbicides are thought to be appropriate in specific contexts. First, Tolley and her colleagues [ 20 ] make the case for including adolescent girls aged 15–17 in HIV prevention trials based on the results of a mixed methods study in Tanzania. She and her colleagues found girls in this age range to be at similar or higher risk of infection to their 18- to 21-year-old counterparts but perceiving themselves at lower risk and under-utilizing prevention services.…”
Section: Understanding Needs Of Specific Groups Of End-usersmentioning
confidence: 99%